Public International Law in the Situation of a Pandemic (Medico Legal Update, 2020)
In recent years, there have been considerable developments in international law with respect to the normativedefinition of the right to health, which includes both health care and healthy conditions. These norms offera framework that shifts the analysis of issues such as disparities in treatment from questions of quality ofcare to matters of social justice. Building on work in social epidemiology, a rights paradigm explicitly linkshealth with laws, policies, and practices that sustain a functional democracy and focuses on accountability